Determination of Malaria Epidemiological Status in Iran’s Malarious Areas as Baseline Information for Implementation of Malaria Elimination Program in Iran - RAEISI, Ahmad (Tehran University of Medical Sciences, 2013)
BACKGROUND: According to willingness of the Ministry of Health, Iran and presence of appropriate conditions for disease elimination, national malaria control program decided to conduct a research to clarify malaria status in 2007 and to provide required information to perform the elimination program. This review is comprised of the basis of national malaria elimination program in vision of 2025, which was started in 2010. METHODS: In this descriptive study, data were analyzed by applications of different variables at district level. All districts in the three south eastern provinces, in which malaria has local transmission, were considered. Malaria cases has been determined and studied based on the national malaria surveillance system. RESULTS: Since vivax malaria is predominant in Sistan & Baluchestan Province, number of vivax cases is equal to malaria positive cases approximately. The important point is that Nikshahr contains the maximum number of local vivax cases in this province and the maximum number of falciparum cases is reported from Sarbaz district. Among all districts of Hormozgan Province, no case of autochthonous falciparum was detected except in Bandar Jask and one case in Minab. There was no case of autochthonous falciparum in Kerman Province, except in Kahnoj and Ghale Ganj that each of them had one case in 2007. CONCLUSION: It appears that the report of locally transmitted cases in Iran is increasing over the past few years, before starting malaria elimination plan. Since the Afghan refugees started to return to their own country so the main source of reporting of imported malaria cases reduced and local cases would be demonstrated more clearly.